Множинна парадигма іменників у фольклорних текстах із Західного Полісся - Грицевич, Юрій Васильович; Hrytsevych, Yurii V. (Maria Curie-Sklodovska University, Poland, 2017)
The article highlights the issues of forming the plural form of nouns in Western Polissian dialects. The analysis is based on the case study of the folklore texts read with the reliance on the structure pattern modeled in the dialectographical works dealing with the Western Polissian dialect of the Ukrainian language. It has been revealed that ramification of the nouns flexion system in the investigated folklore texts is caused by the typical for Western Polissian dialects phonetic phenomena: specific utilization of the old vowels, positional variations of modern vowels, depalatalization of consonants. The case study of the Western Polissian folklore texts confirms the thesis that folklore is a special kind of stylistic interpretation of oral colloquial speech.
Nouns Plurality Paradigm in the Folklore Texts from Western Polissia
Keywords: inflection; noun; plural; flexion; case; grammatical analogy; Western Polissia; folklore texts